PRODUÇÃO E QUALIDADE DE FRUTOS EM MORANGUEIROS INOCULADOS COM FUNGOS MICORRÍZICOS ARBUSCULARES - Cordeiro, Ely Cristina Negrelli (2018)
The use of mycorrhizal arbuscular fungi may be a helping technology, allowing better absorption of nutrients and stimulating the defense system of vegetables, and besides it allows a better synthesis of bioactive compounds. So, the costs of production might decrease and the culture systems may become more sustainable and committed to the environment. The present work had as its goal to evaluate the influence of mycorrhizal arbuscular fungi in agronomic, physiologic and quality compounds in fruits of strawberry cultivars. The evaluated cultivars were Camarosa, Aromas, Camino Real, Monterey, Portola, San Andreas and Albion in 2016 and Camarosa, Camino Real, Monterey and Albion in 2017, inoculated and non-inoculated with mycorrhiza. The compounds of production (number of fruits, total yield and mass of fruits) and after harvesting were evaluated (Vitamin C, Titrated Acidity, pH, Soluble Solids, Ratio, Fenolic Compounds, Antocianins, Humidity, Firmness and Color). Besides these analysis, in 2017 were made gas exchange and leaf area analysis. In the production alaysis the inoculated plants were highlighted in comparison to the non-inoculated in the two years of production. In 2016, to the after harvesting characteristics there was a highlight on the inoculated treatments in the analysis of pH, Soluble Solids, Ratio, Fenolics and Firmness. In 2017, the mycorrhiza gave better results for Titrated Acidity, pH, Soluble Solids, Ratio, Fenolic Compounds and Antocianins. In the color, the mycorrhiza had a highlight on the a* parameter and in chromactivity in 2016. In the avaliation of leaf area, the inoculating treatment was effective, such as presented positive responses in the evaluation of gas exchanges. By the present research, the efectiveness of the use of mycorrhizal arbuscular fungi is noted in productivity characteristics, quality and after harvest in the strawberry cultivars.